ChemInform Abstract: Gram‐Scale Ketone Synthesis by Direct Reductive Coupling of Alkyl Iodides with Acid Chlorides. Issue 2 (14th January 2014) - Lu, Wenbin; Liang, Zhuye; Zhang, Yuwei; Wu, Fan; Qian, Qun; Gong, Hegui
Abstract This procedure is also compatible with the application of crude acid chlorides generated in situ by reaction of the corresponding acids with SOCl2.